On fuzzy financial planning model - Md. Tap, Abu Osman; Madi, Elissa Nadia (2010)
Financial Planning Model is adapted with the hybrid of fuzzy logic. The fuzzy logic displays the morphology of the results that help us to think efficiently based on the knowledge systems. The study is done on randomly selected college students in Terengganu. The result shows that students have different spending behaviors based on two different financial sources. Our analysis also shows the pattern of financial planning in the campus and their level of understanding of financial planning.